E = 1 − ( a − 2 2 − a + 2 2 ) ( a − 4 3 a + 2 )
Let a = 2 0 1 6 . If E can be expressed in the form y x , where x and y are coprime positive integers , find x + y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Abhay Kumar see? Someone agrees with me. @Hung Woei Neoh Nice solution!
Log in to reply
What did I agree to?
Log in to reply
Got it thanks!.
You agree with my answer. Abhay feels my answer was wrong and reported the problem.
Log in to reply
@Hobart Pao – No wonder this was the only one without a solution. The rest all have solutions written by Abhay
E ∴ y x ⟶ x + y = 1 − ( a − 2 2 − a + 2 2 ) ( a − 4 3 a + 2 ) = 1 − ( ( a − 2 ) ( a + 2 ) 2 ( a + 2 ) − ( a + 2 ) ( a − 2 ) 2 ( a − 2 ) ) ( 4 4 a − 4 3 a + 2 ) = 1 − ( ( a − 2 ) ( a + 2 ) 2 ( a + 2 ) − 2 ( a − 2 ) ) ( 4 4 a − ( 3 a + 2 ) ) = 1 − ( ( a − 2 ) ( a + 2 ) 2 a + 4 − 2 a + 4 ) ( 4 4 a − 3 a − 2 ) = 1 − ( ( a − 2 ) ( a + 2 ) 8 ) ( 4 ( a − 2 ) ) = 1 − ( 4 ( a − 2 ) ( a + 2 ) 8 ( a − 2 ) ) = 1 − ( ( a + 2 ) 2 ) = 1 − 2 0 1 8 2 = 1 0 0 9 1 0 0 9 − 1 0 0 9 1 = 1 0 0 9 1 0 0 8 = 1 0 0 9 1 0 0 8 = 1 0 0 8 + 1 0 0 9 = 2 0 1 7
Err......I see no difference in the 5th and 6th lines...
Problem Loading...
Note Loading...
Set Loading...
E = 1 − ( a − 2 2 − a + 2 2 ) ( a − 4 3 a + 2 ) = 1 − ( ( a − 2 ) ( a + 2 ) 2 ( a + 2 ) − 2 ( a − 2 ) ) ( 4 4 a − ( 3 a + 2 ) ) = 1 − ( ( a − 2 ) ( a + 2 ) 8 2 ) ( 4 a − 2 ) = 1 − a + 2 2
a = 2 0 1 6 E = 1 − 2 0 1 6 + 2 2 = 1 − 2 0 1 8 2 = 1 − 1 0 0 9 1 = 1 0 0 9 1 0 0 8
⟹ x = 1 0 0 8 , y = 1 0 0 9 , x + y = 1 0 0 8 + 1 0 0 9 = 2 0 1 7